If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3p + 15 = -6 Reorder the terms: 15 + 3p = -6 Solving 15 + 3p = -6 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 3p = -6 + -15 Combine like terms: 15 + -15 = 0 0 + 3p = -6 + -15 3p = -6 + -15 Combine like terms: -6 + -15 = -21 3p = -21 Divide each side by '3'. p = -7 Simplifying p = -7
| n^2-n-10=0 | | 38-n=n-10 | | 38+N=n-10 | | -7x^2+16x-2=0 | | (2n+25)=180-y | | 38-10d=d | | X+4=9x-44 | | ln(x)+ln(x-3)=ln(3x) | | (2n+25)+y=180 | | 3x^2+13x+7=0 | | 2n+25=y | | -4+8(r+7)=100 | | 24+14+d=d-10 | | 2x-23=x+2 | | 17=a-5.5 | | 35+3x=50 | | 2a+3b+3b+1a= | | 2n=4n+108 | | 4.00=17.3075+x | | X+3s=10.1 | | 7-1*5=2 | | 4p^2-4p-24=0 | | 4x+61=8x+9 | | 3x+46=6x+7 | | 2n+25=3n-10 | | sex=2 | | 9+8*0=9 | | 9+8*0=1 | | 5e-3=3e+7 | | 1-6+8=3 | | -x-4+3x+9=-19 | | 2+9-2-6=3 |